Optimal control applied to a stage-structured cassava mosaic disease model with vector feeding behavior - Eva Lusekelo; Mlyashimbi Helikumi; Salamida Daudi; Steady Mushayabasa (Results in Control and Optimization)
Cassava remains Sub-Saharan Africa’s second most crucial staple food crop after maize. However, production of sufficient yields is hampered by pests and diseases. In particular, the whitefly (Bemisia tabaci) has the potential to reduce expected yields by 50% since it directly damages cassava leaves by feeding on phloem, causing chlorosis and abscission. This study develops a novel mathematical model for cassava mosaic disease that incorporates immature and adult whitefly populations. Additionally, the model includes vector feeding behavior since prior studies have shown that vectors exhibit preferences to settle for either healthy or infected hosts. We determined the offspring number and carried out its sensitivity analysis. Additionally, we carried out an optimal control study on the use of insecticides and plant roguing as disease control measures against cassava mosaic disease. Our results show that vector preference and efficiency of disease control strategies plays an important role in shaping the short and long-term dynamics of cassava mosaic disease, which subsequently impacts the design of its optimal control strategies.